Star amphiphilic supramolecular copolymer based on host–guest interaction for electrochemical controlled drug delivery. (6th April 2016) - Peng, Liao; Wang, Zilin; Feng, Anchao; Huo, Meng; Fang, Tommy; Wang, Ke; Wei, Yen; Yuan, Jinying
Abstract: Research interest in electrochemical redox stimulus has grown considerably due to its easy trigger mode, in which the linkers have played important roles, such as the β-cyclodextrin-ferrocene (β-CD-Fc) linker. Star amphiphilic copolymers with well-defined and flexible structures are considered to be excellent choices for drug delivery systems (DDSs). Driven by the idea that using star polymers to improve the biocompatibility and efficiency of the β-CD-Fc-based DDS, we designed and synthesized star polymer 4 arm-poly(ε-caprolactone)-β-CD (4A PCL-CD ) and linear polymer polyethylene glycol-Fc (PEG-Fc ). They can form supramolecular block copolymer4A PCL-CD /Fc-PEG and self-assemble to micelles, which are electrochemical responsive and can be applied as drug carriers for potential controlled release, with higher efficiency and better biocompatibility compared with their linear analogues. Graphical abstract: Micelles were constructed based on 4 arm-poly(ε-caprolactone)-β-CD and polyethylene glycol-Fc, which are electrochemical responsive and can be applied as drug carriers for potential controlled release. Compared with their linear analogues, these micelles have significantly higher drug loading efficiency, better biocompatibility and more stable stable release behaviour, which is of great importance in real applications. Highlights: The supramolecular micelles are based on cyclodextrin-ferrocene linker. Star polymers make the micelles have higher drug loading efficiency. The micelles can reversibly respond to electrochemical stimuli. The micelles can load doxorubicin and release it under regulation of potential. Good biocompatibility endows the micelles wide applications in real-life systems.